The Effect of Using the PLN Mobile Application on PLN Customer Satisfaction (Case Study at PT PLN ULP Teluk Betung) - Putra, Kelvin Pratama; Barusman, Tina Miniawati (Formosa Journal of Multidisciplinary Research, 2024)
This study aims to determine the effect of using the PLN Mobile Application on PLN Mobile Application User Satisfaction. This research is a type of quantitative research by processing primary data using a data collection method through questionnaires given to customers within the scope of PLN ULP Teluk Betung Bandar Lampung. The sample obtained was 100 respondents by taking samples using purposive sampling. The analytical tool in this research uses IBM SPPS Version 2. The analysis method used is multiple linear regression analysis. By using validity test, reality test, t test, and determination coefficient test. The analytical method used is multiple linear regression analysis. The result of this study is that the PLN Mobile application has a significant effect on customer satisfaction.